Adding Security, but Subtracting Safety? Exploring Schools’ use of Multiple Visible Security Measures - Tanner-Smith, Emily E. (American journal of criminal justice, 2018)
In response to continued concerns over crime and violence, schools are increasingly employing visible security measures such as cameras, metal detectors, and security personnel. These security measures are not mutually exclusive, but few studies have considered the relationship between the use of multiple forms of security and youth’s exposure to drugs, fighting, property crime, and firearms at school. To address this issue, we analyzed nationally representative school administrator-reported data from the School Survey on Crime & Safety, using a quasi-experimental design with propensity scores to adjust for potential confounding factors. The results indicated that utilization of multiple security measures reduced the likelihood of exposure to property crime in high schools, but most other security utilization patterns were associated with poorer school safety outcomes. Our findings provide guidance to policymakers in considering whether to use – or expand – visible school security measures in schools.